Medea sulla scena moderna. La tragedia di Ernest Legouvé nell’allestimento parigino di Adelaide Ristori - Puccio, Francesco (Drammaturgia, 2023)
After composing Adrienne Lecouvreur, a drama co-written with Eugène Scribe and starring Rachel, Ernest Legouvé wrote a Médée for her. But the great actress, although she had already agreed to play the part of the protagonist, decided to give it up. The tragedy was then made famous by Adelaide Ristori who, in 1856, staged it at the Théâtre des Italiens in Paris in a translation by the poet Giuseppe Montanelli. The drama, taken on tour to the major international theatres, was repeated for many years, gaining an extraordinary consensus of public and critics and becoming, as Ristori herself noted in Ricordi, a veritable «workhorse» of her repertoire. In writing the text, in fact, Legouvé had chosen a dramaturgical key that would give life to a character far from the Euripidean model: her Medea, despite being guilty of a terrible infanticide, would not have to appear as a negative heroine, but rather as a woman betrayed and abandoned, and above all as a mother forced to renounce the love of her children. The aim of this contribution is to analyse the performance of the tragedy in its Parisian debut, as a specific case study and as an opportunity to reflect on Ristori’s work as an actress on her character, in the perspective of an accentuation of the maternal dimension.